Gambaran Penggunaan Alat Perlindungan Diri Sebagai Universal Precaution Di Instalasi Rawat Inap RSUD Wates Kulonprogo - Anggih Shulchan Yoga Kusuma; Abdul Majid; Surantono Surantono (Caring : Jurnal Keperawatan, 2018)
Universal precaution is important in remembered a lot of diseases which is dangerous such as HIV/AIDS and Hepatitis B virus. One of universal precaution’s branch is using personal protective equipment (PPE) which is being the object of the research. Descriptive research with a survey research study design, located in Wates Hospital, Kulonprogo. The Subjects were 57 nurses employed on Hospitalization Service of Wates Hospital who’s gotten by proportional sampling method. Data analysis was conducted by distributing the frequencies and percents which categorizing the use of Personal Protective Equipment (PPE). The result is the use of The Personal Protective Equipment (PPE) on Hospitalization Service in Wates Hospital, Kulonprogo by most of the nurse (58%) are in quite a well category. Many factors influenced it, such as stock of PPE, motivation, leadership, age, and reward. The recommendation is the head of hospitalizations should be more intensively monitoring the member (nurses) in using PPE by checklist sheet.